SISTEM INFORMASI PENERIMAAN SISWA BARU BERBASIS WEBSITE SDN 3 GERUNG UTARA - Rahmat Suci; Ismarmiaty; Ria Rismayati (Universitas Islam Negeri Mataram, 2024)
In the current era of globalization, very fast, precise and accurate information is needed in running information for its users. Fast and precise information system management is very helpful for an educational institution where the implementers of education themselves need something that can support and facilitate in achieving their targets and goals. With the benefits and convenience of the internet and sophisticated websites, it should be developed in each school to make it easier to manage data. The problems include frequent errors in data processing because of the large number of prospective student applicants that must be processed, the difficulty of searching for student applicant data because the data is in the form of a pile of forms, the inefficiency of time in the selection process by viewing and checking one by one the requirements for the prospective student registration form, and the information obtained by prospective students is not fast because they have to come to school directly. The purpose of this study is to build a new student admissions information system based on a website using the Laravel Framework, which is able to help process new student admissions data at SDN 3 Gerung Utara in order to provide convenience in registering and announcing. The method used in the development of a new student admissions information system based on a website is the waterfall method. This method has several stages, namely the analysis stage, design stage, program code creation stage, testing stage, maintenance stage so that the application produced has advantages in registering and announcing. The results in making this application can help in processing student data and announcements, and can facilitate registration. It can be concluded that this system can help process new student admissions data at SDN 3 Gerung Utara in order to provide convenience in registering and announcing.